A Heuristic Approach to Obtain an Optimal Solution for Unbalanced Transportation Problem - Srinivasan, N.; Seethalakshmy, A. (International Journal of Engineering and Technology, 2018)
This Method is proposed for obtaining an optimal solution for transportation problem. This method gives the optimal solution in lesser iteration. Here find the difference between two consecutive maximum for row-wise and column-wise. In that find the maximum value, for which the minimum is allocated by the minimum supply or demand. Illustration for this method is given with some examples at the end.Â